Fatigue fracture failure analysis of guide valve based on welding defects - Du, Chenyang; Liu, Chang; Li, Xiaowei; Lu, Jianyu; Yuan, Jun; Liu, Baolin (Frontiers in Materials, 2023)
This research paper presents a failure analysis conducted on the guide valve located at the bottom of the primary outlet buffer tank in the reciprocating machine of the diesel hydrogenation unit during its operation. Various methods, including in-situ observation, macroscopic fracture analysis, metallographic analysis, microscopic fracture observation, material composition analysis, and hardness testing, were employed to investigate the cause of the failure. The findings indicate that the failure resulted from insufficient fusion between the valve body and the flange of the guide shower valve during the manufacturing and welding process. This lack of fusion led to fatigue failure of the weld during operation, ultimately resulting in valve cracking and detachment. The presence of fatigue failure is widespread and poses a significant threat in petrochemical plants and their surrounding environments, given the equipment's exposure to alternating working conditions and vibrations. This failure analysis serves as a valuable reference for future quality inspections of petrochemical equipment parts. Additionally, it assists enterprises in mitigating risks throughout the design, installation, and maintenance processes, thereby reducing the likelihood of similar accidents occurring.